A REVIEW ON CLASSROOM MANAGEMENT AT SECONDARY LEVEL IN KHYBER PAKHTUNKHWA - Ms. Qurrat-ul-Aain; Dr. Hafiz Muhammad Irshadullah; Dr. Samreen Mehmood (International Journal of Contemporary Issues in Social Sciences, 2023)
This study looks at the educational resources that are crucial to provide secondary schools in Khyber Pakhtunkhwa a high-quality education. The researcher investigated the suitability of the physical environment, instructional materials, and secondary school resources in order to determine the relationship between these elements and high-quality education. The research questions were (1) What are the required facilities in classroom management? (2) What are the actual facilities in classroom management? (3) What are the gaps in required and actual facilities in classroom management? The paper is a review and for this more than fifteen article were studies and a secondary data. The study found that the study region's students are dealing with issues like a lack of classrooms, furniture, clean water, trained educators in short supply, high student-teacher ratios, and inadequate educational assets, all of which contribute to low-quality education among students and frequently little to no genuine learning. Teachers are powerless in the absence of basic resources in schools, even though they may be competent individuals. Without these tools, Due to lack of fundamental resources in schools, the teachers are helpless while he/she may be a qualified person, without the fundamental teaching aids, A teacher could hardly hope for the high caliber of instruction they provide. There isn't enough training provided for the instructors to stay current and use these trainings to enhance their teaching abilities.